Prevalence of preeclampsia and its associated risk factors in Rajshahi region, Bangladesh - Akhter, Sultana Nasima; Khatun, Rokeya; Shamima, Mosammat Nargis; Sultana, Nahid; Khatun, Amina; Akhtar, Rawshan; Jahan, Nargis; Begum, Monowara; Haque, M. Jawadul; Hassan, Parvez (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Although preeclampsia claims lives of 70,000 mothers and 500,000 newborns each year, in Bangladesh the comprehensive data-sets are not well-documented. We studied the prevalence of preeclampsia, its trend and the associated risk factors in Rajshahi, Bangladesh. Methods: Using a cross-sectional longitudinal design, 90 women hospitalized with preeclampsia in 7 hospitals of Rajshahi, Bangladesh were considered in the study, of which Rajshahi medical college hospital (RMCH) is a tertiary referral hospital. The data were collected by interviewing the patients, physical examinations and analyzing patients’ pathological profile. For statistical analyses, SPSS software was employed. Results: During the five years (2013-2017), RMCH admitted pregnant mothers for delivery or with obstructed complications had increased from 11,523 to 17,201, leading to an increase in preeclamptic patients from 407 to 435. Its prevalence rate (3.21%) was found to be decreased linearly with time. The preeclamptic patients were of 16-40 years, averaging 25.90±0.65 years. The youngest (£20 years) preeclamptic mothers (24%) were at high risk of preeclampsia. The obese (40%) and overweight (29%) preeclamptic mothers experienced severe oedema, headache, vomiting, lower abdominal pain and hyperacidity. About three-fourths of the concerned patients were of lower socio-economic class, of which the majority was below education level 10. The majority were from joint families (58%) who took less than 2.2 L of drinking water per day. Conclusions: The average prevalence preeclampsia rate was 3.21% that was found to decrease linearly with time. The youngest but obese (BMI of ³30 kg/m2) mothers were vulnerable for preeclampsia. Other risk factors include lower socio-economic class, less education, white complexion, joint family type and taking less amount of fluid.